A biomechanical analysis of prognathous and orthognathous insect head capsules: evidence for a many‐to‐one mapping of form to function. (24th March 2018) - Blanke, A.; Pinheiro, M.; Watson, P. J.; Fagan, M. J.
Abstract: Insect head shapes are remarkably variable, but the influences of these changes on biomechanical performance are unclear. Among 'basal' winged insects, such as dragonflies, mayflies, earwigs and stoneflies, some of the most prominent anatomical changes are the general mouthpart orientation, eye size and the connection of the endoskeleton to the head. Here, we assess these variations as well as differing ridge and sclerite configurations using modern engineering methods including multibody dynamics modelling and finite element analysis in order to quantify and compare the influence of anatomical changes on strain in particular head regions and the whole head. We show that a range of peculiar structures such as the genal/subgenal, epistomal and circumocular areas are consistently highly loaded in all species, despite drastically differing morphologies in species with forward‐projecting (prognathous) and downward‐projecting (orthognathous) mouthparts. Sensitivity analyses show that the presence of eyes has a negligible influence on head capsule strain if a circumocular ridge is present. In contrast, the connection of the dorsal endoskeletal arms to the head capsule especially affects overall head loading in species with downward‐projecting mouthparts. Analysis of the relative strains between species for each head region reveals that concerted changes in head substructures such as the subgenal area, the endoskeleton and the epistomal area lead to a consistent relative loading for the whole head capsule and vulnerable structures such as the eyes. It appears that biting‐chewing loads are managed by a system of strengthening ridges on the head capsule irrespective of the general mouthpart and head orientation. Concerted changes in ridge and endoskeleton configuration might allow for more radical anatomical changes such as the general mouthpart orientation, which could be an explanation for the variability of this trait among insects. In an evolutionary context, many‐to‐one mapping of strain patterns onto a relatively similar overall head loading indeed could have fostered the dynamic diversification processes seen in insects.